Artificial Intelligence and its Awareness and Utilization among Dental Students and Private Dental Practitioners at Alkharj, Saudi Arabia - Inderjit Murugendrappa Gowdar; Abdulaziz Abdulsalam Alateeq; Asim Mohammed Abdullah Alnawfal; Abdulaziz Fahd Abdullah Alharbi; Abdulaziz Mohammed Shaya Alhabshan; Saleh Mohammed Salem Aldawsari; Nawaf Abdullah Hussein AlHarbi (Wolters Kluwer Medknow Publications, 2024)
Introduction: Artificial intelligence (AI) is commonly used in the modern day medical system for medical and dental imaging diagnostics, decision support, precision, hospital monitoring, robotic assistants, and so on. All branches of dentistry have a role of AI, like endodontics, cancer diagnosis, and cephalometric analysis. With the advancing technology, dental professionals need to upgrade themselves. Aim of the Study: To assess awareness and attitude of dental students and dental practitioners in Alkharj toward AI. Methodology: A total of 100 dental students from a teaching institute and 100 private dental practitioners participated in the study. A closed-ended questionnaire was used containing 14 questions related to awareness and attitude toward AI. Participation was voluntary. Results: 33% of study participants were aware of the working principle of AI; 68% of study subjects are aware of uses of AI in the dental field. 87% thinks AI helps in radiological diagnosis; 56.5% thinks AI helps in cancer detection. Conclusion: Awareness about AI among study participants was less than 50%. The overall attitude of dental professionals was positive.